Synthesis and characterization of a quaternary nanocomposite based on TiO2/CdS/rGO/Pt and its application in the photoreduction of CO2 to methane under visible light1. Issue 43 (14th May 2015) - Benedetti, J. E.; Bernardo, D. R.; Morais, A.; Bettini, Jefferson; Nogueira, A. F.
<x xml:space="preserve">Abstract</x> "Together we are stronger": For the first time, TiO2/CdS/rGO/Pt nanocomposite was used as a catalyst for the photocatalytic reduction of CO2 to CH4.